Explosive training and heavy weight training are effective for improving running economy in endurance athletes: A systematic review and meta-analysis - Denadai, B. S.; Alves de Aguiar, R.; Coelho Rabello de Lima, L.; Coelho Greco, C.; Caputo, F. (Sports Medicine, 2017)
Several strategies have been used to improve running economy (RE). Defined as the oxygen uptake required at a given submaximal running velocity, it has been considered a key aerobic parameter related to endurance running performance. In this context, concurrent strength and endurance training has been considered an effective method, although conclusions on the optimal concurrent training cannot yet be drawn. Objective: To evaluate the effect of concurrent training on RE in endurance running athletes and identify the effects of subject characteristics and concurrent training variables on the magnitude of RE improvement. Methods: We conducted a computerized search of the PubMed and Web of Science databases, and references of original studies were searched for further relevant studies. The analysis comprised 20 effects in 16 relevant studies published up to August 2015. The outcomes were calculated as the difference in percentage change between control and experimental groups (% change) and data were presented as mean ± 95 % confidence limit. Meta-analyses were performed using a random-effects model and, in addition, simple and multiple meta-regression analyses were used to identify effects of age, training status, number of sessions per week, training duration, type of strength training, and neuromuscular performance on % change in RE. Results: The concurrent training program had a small beneficial effect on RE (% change = -3.93 ± 1.19 %; p < 0.001). In addition, explosive (% change = -4.83 ± 1.53; p < 0.001) and heavy weight (% change = -3.65 ± 2.74; p = 0.009) training programs produced similar improvements in RE, while isometric training (% change = -2.20 ± 4.37; p = 0.324) in selected studies did not induce a significant effect. The multiple linear meta-regression analysis showed that all the differences between % changes could be explained by including the above-mentioned characteristics of subjects and weight training program elements. This model showed that the magnitude of the % change in RE was larger for longer training duration (ß = -0.83 ± 0.72, p = 0.02). Conclusion: Explosive training and heavy weight training are effective concurrent training methods aiming to improve RE within a few weeks. However, long-term training programs seem to be necessary when the largest possible improvement in RE is desired.